Analisis Kepentingan Indonesia Dalam Masyarakat Ekonomi ASEAN - Wicaksa, Arif; Laksono, Ailsa; Aisyah, Aisyah (Department of International Relations, Universitas Mulawarman, 2025)
This study describes the factors inhibiting the optimization of Indonesia's interests within the ASEAN Economic Community (AEC), employing Keohane and Nye's theoretical framework of Asymmetric Interdependence. Utilizing a qualitative library research method, the study examines Indonesia's position across four key areas: trade structure, investment flows, skilled labor mobility, and integration into Global Value Chains (GVCs). The findings reveal that Indonesia's relationship with fellow MEA member states is fundamentally asymmetrical. Indonesia remains locked into the role of a raw material supplier, a destination for extractive-consumptive investment, and an exporter of informal labor, while simultaneously being a net importer of high-value manufactured goods, a user of foreign skilled labor, and a consumer of final products. This pattern creates long-term structural vulnerabilities, weakens Indonesia's bargaining position, and hinders its economic transformation. The study concludes that Asymmetric Interdependence is a fundamental inhibiting factor that constrains Indonesia's ability to optimally leverage the MEA, necessitating strategic and long-term-oriented corrective policies.